2020
DOI: 10.1029/2020gc009177
|View full text |Cite
|
Sign up to set email alerts
|

A Lithosphere‐Asthenosphere Boundary and Partial Melt Estimated Using Marine Magnetotelluric Data at the Central Middle Atlantic Ridge

Abstract: The differential motion between the lithosphere and the asthenosphere is aseismic, so the magnetotelluric (MT) method plays an important role in studying the depth and nature of the lithosphere‐asthenosphere boundary (LAB). In March 2016, we deployed 39 marine MT instruments across the Middle Atlantic Ridge (MAR), 2,000 km away from the African coast, to study the evolution of the LAB with ages out to 45 million years (My). The MT acquisition time was limited to about 60 days by battery life. After analyzing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 90 publications
7
57
0
Order By: Relevance
“…Melt may pond at the base of the lithosphere in channels (Sim et al, 2020; Sparks & Parmentier, 1991), as suggested from active source studies in the Pacific (Stern et al, 2015) and near our study region further to the north (Mehouachi & Singh, 2018). Low‐resistivity channels, consistent with the presence of partial melt, have also been imaged within our study region using MT (Wang et al, 2020). The channels are likely fed by the buoyant upwellings we observe at greater depths.…”
Section: Discussionsupporting
confidence: 79%
“…Melt may pond at the base of the lithosphere in channels (Sim et al, 2020; Sparks & Parmentier, 1991), as suggested from active source studies in the Pacific (Stern et al, 2015) and near our study region further to the north (Mehouachi & Singh, 2018). Low‐resistivity channels, consistent with the presence of partial melt, have also been imaged within our study region using MT (Wang et al, 2020). The channels are likely fed by the buoyant upwellings we observe at greater depths.…”
Section: Discussionsupporting
confidence: 79%
“…Beneath 70 Myr old Pacific lithosphere, there is general agreement between the 1‐D seismic velocity profile and the 1‐D resistivity profile, where the LVZ is characterized by a small volume of interconnected melt (Selway & O'Donnell, 2019). Beneath young seafloor near the equatorial Mid‐Atlantic Ridge there is good agreement between the location of the slowest seismic velocity anomalies and the lowest resistivity anomalies, which also generally occur beneath the strongest LAB phases in Sp imaging (Harmon et al, 2020; Rychert et al, 2019; Wang et al, 2020). Beneath the Piedmont and Coastal Plain in the southeastern United States, the electrical LAB is ~50 km deeper than the seismic LAB obtained from seismic tomography (Murphy & Egbert, 2019).…”
Section: Recent Observational Constraints On the Depth And Sharpness mentioning
confidence: 81%
“…Thus, for example, Naif et al (2013) used MT data to detect enhanced conductivity in the plate‐motion direction for partial melts at the LAB, interpreted as shearing. Chesley et al (2019) observed a similar anisotropy in subsolidus lithospheric mantle using a related electrical method (controlled‐source sounding), and Wang et al (2020) estimated melt fraction at the LAB beneath Mid‐Atlantic Ridge using MT data.…”
Section: Recent Observational Constraints On the Depth And Sharpness mentioning
confidence: 95%
See 2 more Smart Citations